DETERMINAN KUALITAS HIDUP PADA LANSIA DENGAN PENYAKIT KRONIS DI RW 04 KELURAHAN CITAYAM BOGOR - Nurfatma Silvia, (2020)
Elderly is someone who has reached the age of 60 years and above, and is also called the aging process, where a person will change physically, psychologically and socially. This condition is interrelated with natural processes that occur during aging and affect the quality of life. The purpose of this study was to determine the factors associated with quality of life in the elderly in RW 04, Citayam Urban Village. This study uses a cross sectional design. The technique used to collect data is the purposive sampling method. The sample used is the elderly who have chronic diseases (hypertension, diabetes mellitus, and gout) totaling 40 respondents. Analysis of the data used is the chi-square and independent T test. Variables that have a significant relationship with the quality of life of the elderly are the level of depression with the value (p-value = 0.001 <0.05) and the level of anxiety with the value (p-value = 0.008 <0.05). And variables that have no significant relationship with the quality of life of the elderly are age (p-value = 0.369), gender (p-value = 0.726), marital status (p-value = 0324), last education (p-value = 0.427 ), work (p-value = 0554), hypertension (p-value = 0.567), DM (p-value = 0.550), (p-value = 1,000),), stress level (p-value = 0.022) and support (p-value = 0.763). The research suggestion is that the Puskesmas should improve the health and quality of life of the elderly, especially at the level of depression and anxiety by coordinating with cadres in RW 04, Citayam Urban Village.